Application of Unmanned Aerial Vehicle (UAV) for Slope Mapping at Pahang Matriculation College, Malaysia - Mohd Fakhrurrazi, Ishak; Muhammad Farhan, Zolkepli; M. Y. M., Yunus; M. S. I., Zaini; M. S., Wahap; A. M., Yasin; M. H., Sidik; M. A., Hezmi (Elsevier Ltd., 2021)
This paper discusses the applications of unmanned aerial vehicle (UAV) for slope mapping which located at Pahang Matriculation College, Malaysia. Mapping is very important to obtain the terrain profiles for study area. By using UAV and commercial software, important information of slopes including perimeter, area and volume will be determined. With the development of modern technology, the utilization of UAV to gather data for mapping becoming easier as it is quick, reliable, precise, cost-effective and also easily to operate. High imagery quality is essential for the effectiveness and nature of normal mapping output such as Digital Surface Model (DSM) and Digital Orthophoto. With the help of established software, the dimensions of selected study area can be determined easily which can be considered as the main interest in this study. In addition to that, the cross-section of selected area can be obtained which help to determine the highest and lowest point of each area together with the terrain profiles. These slope profiles are determined according to their respective axis (vertical and horizontal) since both axis give different terrain profiles for each slope. Other than that, this research was further extended by determining the potential slope hazard based on their respective angles. These determinations are very important as early precautionary steps for engineers and researchers to prevent from any danger, injuries and accidents that for worse may cause fatalities.